Conditions and Prerequisites for the Establishment of Environmental Forensics in the Republic of Belarus - D. E. Kuzmenkov; A. N. Khokh; S. V. Rubinchik (Теория и практика судебной экспертизы, 2017)
The article considers the prerequisites and conditions for the establishment of environmental forensics as a new branch of forensic science in the Republic of Belarus. The authors advocate conducting this type of examinations at special competency centers, such as the Scientific and Practical Center (SPC) of the State Forensic Examination Committee of the Republic of Belarus